Stress and birth outcomes : evidence from terrorist attacks in Colombia (2007)
This paper estimates the impact of random terrorist attacks (landmines) in Colombia on the health of babies born between 1998 and 2003. The results suggest that these types of terrorist activities that occur during a woman's first trimester of pregnancy have a negative and significant impact on child health outcomes such as birth weight and preterm deliveries, and behaviors such as use of prenatal care. These findings persist when mother fixed effects are included, suggesting that neither observable nor unobservable characteristics of the mothers are driving the results. The paper contributes to the existing literature by identifying yet another important channel through which violence affects economic well being. Given that studies have found a strong link between Low Birth Weight (LBW) and short and long-term socioeconomic outcomes, the negative consequences of violence identified in this paper may have long-term effects on economic activity.